IMPLEMENTASI PUBLIC-PRIVATE-PARTNERSHIP (PPP) DALAM PELESTARIAN KAWASAN CAGAR BUDAYA PERKOTAAN - Christin Dameria; Petrus Natalivan Indradjati (Universitas Batam, 2022)
Once the central of economic, urban heritage has been experiencing physical degradation thus abandoned. However, urban heritage conservation is almost impossible if relying on government resources solely. Public-Partner-Partnership (PPP) has been seen as the right approach to solve the problem. This paper argues that the partnership should be carefully reviewed when implemented in the urban heritage conservation context. Other than the size of the program is smaller and specific, the partnership must also consider the area context, the vulnerability of the area, and the presence of people who live and carry out activities in the area. Therefore, there are requirements when adopting PPP in the urban heritage conservation context, namely: (1) entrepreneurial government, as a public sector, who can create an efficient and adaptive bureaucracy, must also have strong leadership in managing conflict of interest among the stakeholder, especially due to the involvement of profit oriented private sectors; (2) market orientation of the private sector must appreciate the cultural significant values of urban heritage and place the community as more than just consumers; (3) the community, as the third sector, must have a clear position in the partnership and be accompanied by a mediator who can also protect the interest of the community.Â